ASSESSMENT OF QUALITY OF LIFE OF HYPERTENSIVE USERS OF A HEALTH CARE CENTER - Kruger, Ana Paula; Mergener, Michelle; Pozzobon, Adriane; Moreira, Thaís Rodrigues (Journal of Health Care, 2015)
Introduction: Hypertension is one of the most prevalent diseases in the world, reaching about 30%of adults worldwide. Among the factors that increase blood pressure stand out obesity, stress and inadequatenutrition. Objectives: The aim of this study was to evaluate the quality of life and to assess itscorrelation with the anthropometric assessment of hypertensive patients. Materials and Methods: Weevaluated 51 patients by measuring their of body weight, height, body mass index, waist circumference,triceps skinfold thickness, arm muscle circumference, blood pressure measurement and application of theWHOQOL-bref questionnaire to assess the quality of life. Results: Through the body mass index, 53%(n=27) were overweight, 45% (n=23) normal weight and 2% (n=1) thinness. For the arm muscle circumference,82% (n=42) were considered normal, and on waist circumference, 96% (n=49) were at risk ofdeveloping cardiovascular disease, and 90% (n=46) of patients had high blood pressure. In assessing theWHOQOL-bref, it was observed that the greater the age of individuals, the worst were the perceptionsregarding areas relating to the environment and overall quality of life. The overall score for quality of lifeof the non-elderly group was not significantly higher than in the older group. Conclusions: The majorityof individuals in the sample have risk of developing cardiovascular diseases and overweight. It can be seenthat the assessed non-elderly individuals have a better perception of quality of life, with a higher score inthe WHOQOL-bref questionnaire when compared to older people.
Keywords: Hypertension; quality of life; body mass index.